RANCANG BANGUN PEMBUKA DAN PENUTUP TIRAI OTOMATIS BERBASIS INTERNET OF THINGS - Fahriza, Tavana Ayu; M. A. Akbareziansyah; Saputra, Zanu; Andik Setiawan, I Made (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Blinds or curtains serve to provide privacy, protect the room from direct sunlight, and prevent outside views. In addition, curtains can also protect the skin from the risk of hyperpigmentation due to excessive sun exposure. This research system develops an iot-based automatic curtain opening and closing tool, using the bylnk application to monitor and be able to open and close the curtains automatically, with nodemcu esp8266 as a curtain control system and ldr sensor and ic rtc as additional input to monitor the curtains. The results of the development of this tool show that the system is developing and functioning properly to be able to monitor and be able to open and close the curtains through the blynk application contained in the smartphone and automatically through the rtc ic whose time has been determined.